2014
DOI: 10.1039/c4pp00186a
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy downregulates the function of regulatory T cells in patients with esophageal squamous cell carcinoma

Abstract: Photodynamic therapy (PDT) by selective photosensitization of cancer cells and subsequent laser application results in local tumor necrosis. However, the effects of PDT on immune function, which may depend on the type of immune response, are controversial. We investigated the immunological changes induced by PDT and the effect of PDT on level and function of regulatory T cells (Treg) in patients with invasive esophageal squamous cell carcinoma (ESCC). We analyzed patient's blood samples before and after PDT. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…This clinical effect of low‐dose PDT on antitumor immunity is in line with preclinical studies showing that low‐dose PDT enhanced antitumor immunity more effectively than high‐dose PDT (5,62). PDT was also shown to reduce immunosuppression, through reduction in Tregs, in invasive esophageal squamous cell carcinoma (ESCC) patients (8).…”
Section: Components Of Pdt: Photosensitizer Light and Molecular Oxygenmentioning
confidence: 99%
“…This clinical effect of low‐dose PDT on antitumor immunity is in line with preclinical studies showing that low‐dose PDT enhanced antitumor immunity more effectively than high‐dose PDT (5,62). PDT was also shown to reduce immunosuppression, through reduction in Tregs, in invasive esophageal squamous cell carcinoma (ESCC) patients (8).…”
Section: Components Of Pdt: Photosensitizer Light and Molecular Oxygenmentioning
confidence: 99%
“…This was accompanied by a significant inhibition of tumor growth upon challenge with live LLC cells [40]. In a clinical setting, blood analysis of patients with esophageal squamous cell carcinoma demonstrated that PDT with the PS Photofrin ® abolished the suppressive function of peripheral Treg, but had no effect on Treg numbers [72]. Taken together, these studies indicate effects of PDT on Treg, which have to be elucidated in order to harness the potential of PDT to break tumor-promoting immune suppression.…”
Section: Pdt and Adaptive Immunitymentioning
confidence: 99%
“…Therefore, in addition to having less effector T cells due to increased Pc 4 uptake and PDT-dependent apoptosis, there would be a higher ratio of Treg:Teff cells and a net suppressive environment which would result in a more effective suppression of a responding effector T cell response. Whether this will be demonstrable in autoinflammatory disorders and cancer remains to be seen, as a decrease in Treg in situ in esophageal cancer following PDT with Photofrin was not observed (30). Extensive investigations using various PDT photosensitizers have previously revealed preferential uptake of photosensitizers by 1.)…”
Section: Discussionmentioning
confidence: 99%